2020
DOI: 10.3390/ijms21186863
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Smoothened in Cancer

Abstract: Smoothened (SMO) belongs to the Hedgehog (HH) signaling pathway, which regulates cell growth, migration, invasion and stem cells in cancer. The HH signaling pathway includes both canonical and noncanonical pathways. The canonical HH pathway functions through major HH molecules such as HH ligands, PTCH, SMO and GLI, whereas the noncanonical HH pathway involves the activation of SMO or GLI through other pathways. The role of SMO has been discussed in different types of cancer, including breast, liver, pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 152 publications
0
31
0
Order By: Relevance
“…Additionally, the overexpression of Smo is significantly associated with poor prognosis in GBM patients [ 131 ]. Smo expression inhibition, which suppresses GBM proliferation, migration, invasion, and tumorigenesis, further supports this observation [ 132 ].…”
Section: Dysregulated Signaling Pathways Associated With Gbm Pathomentioning
confidence: 65%
“…Additionally, the overexpression of Smo is significantly associated with poor prognosis in GBM patients [ 131 ]. Smo expression inhibition, which suppresses GBM proliferation, migration, invasion, and tumorigenesis, further supports this observation [ 132 ].…”
Section: Dysregulated Signaling Pathways Associated With Gbm Pathomentioning
confidence: 65%
“…Additionally, to better acquire knowledge of the processes the TFs participate in each of the cell types, we performed a pathway enrichment analysis. This evaluation revealed that in TP astrocyte, TFs ZNF878 and CREB3L4 are involved in highest number of processes such as signal transduction downstream of smoothened protein which is involved in hedgehog signaling [36] , activation of phospholipase C activity and peroxisome, positive regulation of translation, respectively ( Fig. 7 A) .…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that SMO activates the Gli1 in the canonical Hedgehog pathway 20 , 24 . To investigate whether SMO is implicated in Rab1A-mediated Gli1 upregulation, we detected SMO protein expression in Rab1A-depleted and Rab1A-overexpressed CRC cells.…”
Section: Resultsmentioning
confidence: 99%
“…The Hedgehog (HH) signaling pathway is a conserved pathway involved in cell growth and tissue patterning 18 20 . In mammals, HH signaling initiates with binding of one of the three ligands (Indian Hedgehog (IHH), Sonic Hedgehog (SHH) and Desert Hedgehog (DHH)) to the protein patched homolog (PTCH), causing the release of the suppressed transmembrane protein Smoothened (SMO).…”
Section: Introductionmentioning
confidence: 99%